When breath becomes air - Kalanithi, Paul (Random House, 2016)
"At the age of thirty-six, on the verge of completing a decade's worth of training as a neurosurgeon, Paul Kalanithi was diagnosed with stage IV lung cancer. One day he was a doctor treating the dying, and the next he was a patient struggling to live. And just like that, the future he and his wife had imagined evaporated. When Breath Becomes Air chronicles Kalanithi's transformation from a naïve medical student 'possessed, ' as he wrote, 'by the question of what, given that all organisms die, makes a virtuous and meaningful life' into a neurosurgeon at Stanford working in the brain, the most critical place for human identity, and finally into a patient and new father confronting his own mortality"--Publisher's website.